Funiculí, Funiculà? The cultural bait of italianity and the process of urban gentrification in the center of Nova Veneza - SC (PerCursos, 2022)
The article initiates an investigation into a possible process of urban gentrification in a city with low population density and a history of Italian immigration: the city of Nova Veneza | Santa Catarina. The study aimed to understand the initial effects of the repeated architectural reforms in Humberto Bortoluzzi Square – driven by the investments of the local government – in the established uses of that space and in the urban transformation of its surroundings, and the close correlation with the discourse of italianity. To that end, we start from the following question: how does the urban reforms of the square impact its use and the reconfiguration of its surroundings? It was a qualitative research, whose data generation instruments used were participant observation, semi-structured interviews and informal conversations. The textual organization is presented as a narrative, in order to assist the textual form, the analytical process, the spatial description and any subjectivities. In the theoretical field, the references used are from authors from Urban Anthropology and Urban Planning.
Keywords: Nova Veneza; gentrification; urban reforms; Humberto Bortoluzzi Square; tourism